Democratic inequality in the austerity state. Issue 3 (December 2013) - Offe, Claus
<x xml:space="preserve">Abstract</x> Claus Offe argues that a natural tendency for democracies to exclude the poorest has been exacerbated by austerity policies and a diminished offer from an 'emaciated state'.